The Seepage Tensor of the Multiparameter Model of Pipe Element in Fractured Rock Mass - Junqi, Wang; Ziyan, Wang; Xiaoting, Wei (Frontiers in Built Environment, 2022)
Based on the measured fracture production of the rock body in the field, the disc fracture hypothesis is used to generate three groups of fractures to form a fracture network by Monte- Carlo method. The three-dimensional fracture network is simplified into a spatial one-dimensional pipe element model based on the hypothesis of water channel flow in the fractures, and the equivalent pipe diameter of the pipe element is considered to be linearly related to the fracture width. The equivalent permeability tensor is obtained by using genetic algorithm to obtain the ratio of equivalent pipe diameter to aperture size for each group of fissures, and compared with the equivalent permeability tensor obtained by the overall single-parameter model and direct algorithm. In comparison with the measured permeability tensor, it is concluded that the multi-parameter model can better characterize the permeability tensor than the single-parameter model.